จินตนาการทางเพศของผู้หญิงผ่านนิตยสารวัยรุ่น - เจิมสิริ เหลืองศุภภรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study female sexual fantasy expressed through teen-magazines. Data were collected mainly from the two mass circulation teen-magazines named Ther Kub Chan and The Boy for the volume of 2001, 24 issues totally as well as in-depth interview magazines readers. Results of the research are as follow: 1. Teen -magazines presented suvual fantasy in terms of verbal and non-verbal language in 2 levels--mainifest and latent level of meaning. Non-verbal language presented in 4 categories including photograph, drawing picture, colorign and symbol. Moreover, the sexual fantasy content of teen-magazines could be categorized into finve topics, including (i) romance, (ii) fashion and beauty, (iii) personal/domestic, (iv) popular music, and (v) others. All reflected sexual fantasy of Thai and Western context. 2. Teenagers used the characteristics of suxual fantasy in teen-magazines to create meanings of sexual fantasy. The meanings were included (i) romance-myth of romance, such as love is a fashion, marriage is woman s aim of life, love is a destiny, (ii) the exposure of sexual relations, for instance, polygamy, homesexual and contradiction between cover and uncover sexual feelings, and (iii) pattern of ideal woman and fantasy of romantic hero. 3. Consideration magaziness as a sphere to construct the meanings of female sexual fantasy, three types of construction were found: consensus, resistance, and negotiation. The topics that appeared among these three types were, for instance, sexy dressing, love and sexual relations, nightlife, and homosexual. the research concluded that teen-magazines could provide a space for negotiation of sexual fantasy for female teenagers. It was also found an attempt to compromise sexual values between those of adult or traditional values and those of teenagers.